Microsurgical Fibular Flap for Pelvic Ring Reconstruction after Periacetabular Tumor Resection - Yu, Guangrong; Zhang, Feng; Zhou, Jiaqian; Chang, Shimin; Cheng, Liming; Jia, Yongwei; Li, Haifeng; Lineaweaver, William C (Journal of Reconstructive Microsurgery, 2007)
Reconstruction after resection of tumor about the acetabulum represents a considerable challenge in reconstructive surgery. Between 1999 and 2003, three patients with periacetabular tumors underwent tumor resections (Ennecking type B) and pelvic ring reconstruction with microsurgical fibular flaps. Histological diagnosis showed oseosarcoma, giant cell tumor, and aneurysmoid bone cyst. All patients survived surgery without complications. The follow-up for patients ranged from 14 to 42 months. The average time for bone healing and full weight bearing was 13.6 weeks after surgery. In evaluations of the functional outcome using Enneking scoring system, two reached the score of excellent (≥ 23 points), and one reached the score of good (15 to 22 points). This report shows our experience in use of microsurgical fibular flaps for arthrodesis of the hip after periacetabular tumor resection, which restores the continuity of the pelvic ring with minimal shortening of the limb.
Keywords: Pelvis; reconstruction; fibular; microsurgery